Retorika Ustadz Jefrizal dalam Berdakwah di Kecamatan Bangko Kabupaten Rokan Hilir Provinsi Riau - Nur Azana; Azhar azhar; Mutiawati Mutiawati (Maktabatun: Jurnal Perpustakaan dan Informasi, 2023)
This study aims to find out how Ustadz Jefrizal's rhetoric is in preaching in Bangko District, Rokan Hilir Regency, Riau Province, knowing the language style, voice style and gesture style that is applied. This study uses a qualitative method. Data collection was carried out by means of observation and documentation obtained directly in the field as well as documents from sources related to research. And the informant in the study as well as the object analyzed in this study was Ustadz Jefrizal. From the analysis of the data in the field, it was found that Ustadz Jefrizal's rhetoric in preaching was seen in terms of style of language, style of gestures and style of voice which was quite varied and was able to adapt to the material presented so that listeners could easily understand and understand the material presented. Ustadz Jefrizal in his lectures predominantly used unofficial language style and conversational language style, Climax, Paraleism, Repetition; Epizeuksis, Anaphora and Anadiplosis, Rhetoric; Alliteration, Assonance, Eufimismus, Litotes, and erotesis, as well as Simile and Allegory, pay attention to tone of voice such as Pitch, Pause and Rate and non-monotonous gestures